2009
DOI: 10.1002/adfm.200900283
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaics Based on Hybridization of Effective Dye‐Sensitized Titanium Oxide and Hole‐Conductive Polymer P3HT

Abstract: Here, the fabrication of quasi‐solid‐state TiO2/dye/poly(3‐hexylthiophene) (P3HT) solar cells is reported, in which the dyes with oleophilic thienyl groups were employed and ionic liquid (IL), 1‐ethyl‐3‐methylimidazolium (EMIm) containing lithium bis(trifluromethanesulfone)amide (Li‐TFSI) and 4‐tert‐butylpyridine (t‐BP) are assembled with dyed TiO2 surfaces. One of the devices gave a high conversion efficiency of up to 2.70% under 1 sun illumination. The excellent performance is ascribed to successful molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 31 publications
(59 reference statements)
3
86
0
Order By: Relevance
“…mesoporous fi lms with polymers, [ 7 ] combined with the previously postulated poor charge transport of P3HT in random mesoporous channels. [ 8 ] Two similar studies from Jiang et al [ 1 ] and from Zhu et al [ 2 ] on P3HT based DSSCs showed that the addition of lithium salts and tert-butyl pyridine signifi cantly increased the effi ciency in presence of a metal-free organic dye. The origin of this improvement is ascribed in one instance to a slight deepening of the dye HOMO level upon the addition of lithium salts enhancing the hole-transfer effi ciency, [ 9 ] and in the other case to be due to enhanced charge separation effi ciency.…”
Section: Infl Uence Of Ion Induced Local Coulomb Field and Polarity Omentioning
confidence: 93%
“…mesoporous fi lms with polymers, [ 7 ] combined with the previously postulated poor charge transport of P3HT in random mesoporous channels. [ 8 ] Two similar studies from Jiang et al [ 1 ] and from Zhu et al [ 2 ] on P3HT based DSSCs showed that the addition of lithium salts and tert-butyl pyridine signifi cantly increased the effi ciency in presence of a metal-free organic dye. The origin of this improvement is ascribed in one instance to a slight deepening of the dye HOMO level upon the addition of lithium salts enhancing the hole-transfer effi ciency, [ 9 ] and in the other case to be due to enhanced charge separation effi ciency.…”
Section: Infl Uence Of Ion Induced Local Coulomb Field and Polarity Omentioning
confidence: 93%
“…[ 19 ] Another possibility is the utilization of p-type conducting polymers, e.g., polypyrrole, polyaniline, polydiacetylene, poly (3-octylthiopehene), and poly(3,4-ethylenedioxythiophene) (PEDOT). [20][21][22][23][24][25][26] These polymers are advantageous over other small molecules due to their low cost, good stability, simple fabrication using spin-coating, and easy preparation of designable structures. Recently, Ho et al reported an iodine (I 2 )-free ssDSSC using polyaniline/carbon black composite with imidazolium iodide derivatives, which effectively generates I − / I 3 − redox couples without addition of iodine (I 2 ).…”
mentioning
confidence: 99%
“…The result indicated that the dye/spiro-OMeTAD interfaces are self-organized by oleophilic interaction resulting in improved photocurrent and efficiency. Similarly, Jiang et al [74] also reported the dyes with oleophilic thienyl groups, which show power conversion efficiency of up to 2.7%. Such improvement in PCE is also believed because of self-organized interface between dye molecules and polymer material.…”
Section: Solid-state Dye-sensitized Solar Cell Using Conjugated Polymmentioning
confidence: 79%
“…Various triarylamine-based polymers [60][61][62][63], poly(3-alkylthiophene)s [64][65][66][67][68][69][70][71][72][73][74][75][76], polypyrrole [77][78][79][80], polyaniline [81][82][83][84][85], are studied as HTMs in solid-state DSSCs. The polymers cast from solutions must penetrate into the pores between the nanoparticles and should form a good contact with the absorbed dye.…”
Section: Solid-state Dye-sensitized Solar Cell Using Conjugated Polymmentioning
confidence: 99%